The Impact of Participation in the Clean Beach Program and Educational Seminars on the Awareness of Tourists on Kuta Beach, Bali - Santi Diwyarthi, Ni Desak Made; Adi Pratama, I Wayan (Westscience Press, 2025)
This study examines the impact of participation in the Clean Beach Program and educational seminars on the environmental awareness of tourists visiting Kuta Beach, Bali. Employing a quantitative research approach, data were collected from 90 respondents using a structured questionnaire. The findings reveal a significant positive effect of these initiatives on environmental awareness, with participants engaging in both activities demonstrating the highest awareness levels. The study highlights the complementary nature of participatory and educational approaches in fostering pro-environmental attitudes among tourists. These results offer valuable insights for developing sustainable tourism programs aimed at enhancing environmental consciousness.